2016
DOI: 10.1111/acel.12518
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule compounds that induce cellular senescence

Abstract: SummaryTo date, dozens of stress-induced cellular senescence phenotypes have been reported. These cellular senescence states may differ substantially from each other, as well as from replicative senescence through the presence of specific senescence features. Here, we attempted to catalog virtually all of the cellular senescencelike states that can be induced by low molecular weight compounds. We summarized biological markers, molecular pathways involved in senescence establishment, and specific traits of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
136
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 165 publications
(54 reference statements)
4
136
0
Order By: Relevance
“…Namely, HU provokes a deoxyribonucleotides, double‐strand DNA breaks near to replication forks, and inhibits both nuclear and mitochondrial DNA replication, thus causing cellular and mitochondrial dysfunctions . Moreover, HU is a DNA replication stress inducer and can induce senescence‐like phenotype in both transformed and primary cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, HU provokes a deoxyribonucleotides, double‐strand DNA breaks near to replication forks, and inhibits both nuclear and mitochondrial DNA replication, thus causing cellular and mitochondrial dysfunctions . Moreover, HU is a DNA replication stress inducer and can induce senescence‐like phenotype in both transformed and primary cells .…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapeutic drugs can induce the persistent presence of senescent cells in normal noncancerous tissues . In vitro studies have demonstrated that different transformed cell lines and primary cells, such as fibroblasts and mesenchymal stromal cells (MSC) can display a senescence‐like phenotype . Although MSC circulate at a very low level in healthy individuals, peripheral blood MSC (PBMSC) are increased in pathological conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, using literature mining, we identified studies showing the association with longevity of cAMP analogues [28], selenium [29,30] and tanespimycin [31,32]. In contrast, we also found evidence for the DNA-mediated, pro-ageing (anti-longevity) effects of doxorubicin [33], cisplatin [34] and hydrogen peroxide [35]. We performed an interaction-based similarity analysis and found that the genotoxic compounds cluster separately from the other drugs, suggesting that they have a similar mechanism of action (S2 text).…”
Section: Resultsmentioning
confidence: 99%
“…However, cytoplasmic p16 has also been reported as correlating with the absence of metastasis in other cancer types, such as melanoma [7]. Commonly used chemotherapeutic drugs such as etoposide and doxorubicin can increase p16 protein levels and induce senescence [8], but whether and to what extent these agents affect p16 localization has not been fully explored. Interestingly, p16 does not have a known nuclear localization signal (NLS) or a nuclear export signal (NES) [9], suggesting that an indirect mechanism of intracellular transport is responsible for shuttling p16 between different cellular compartments [10].…”
Section: Introductionmentioning
confidence: 99%